Life Cycle Assessment of Titania Perovskite Solar Cell Technology for Sustainable Design and Manufacturing. Issue 22 (22nd October 2015) - Zhang, Jingyi; Gao, Xianfeng; Deng, Yelin; Li, Bingbing; Yuan, Chris
Abstract: Perovskite solar cells have attracted enormous attention in recent years due to their low cost and superior technical performance. However, the use of toxic metals, such as lead, in the perovskite dye and toxic chemicals in perovskite solar cell manufacturing causes grave concerns for its environmental performance. To understand and facilitate the sustainable development of perovskite solar cell technology from its design to manufacturing, a comprehensive environmental impact assessment has been conducted on titanium dioxide nanotube based perovskite solar cells by using an attributional life cycle assessment approach, from cradle to gate, with manufacturing data from our laboratory‐scale experiments and upstream data collected from professional databases and the literature. The results indicate that the perovskite dye is the primary source of environmental impact, associated with 64.77 % total embodied energy and 31.38 % embodied materials consumption, contributing to more than 50 % of the life cycle impact in almost all impact categories, although lead used in the perovskite dye only contributes to about 1.14 % of the human toxicity potential. A comparison of perovskite solar cells with commercial silicon and cadmium–tellurium solar cells reveals that perovskite solar cells could be a promising alternative technology for future large‐scale industrial applications. Abstract : Improved procedures : A robust life cycle environmental impact study of emerging perovskite solar cell technology with a TiO2 nanotube anode and liquid electrolyte is presented, with the aim of understanding and facilitating the sustainable design and manufacturing of perovskite solar technology in this early developmental stage.